Título Padrão: Novo registro do tubarão-de-seis-guelras, Hexanchus griseus (Chondrichthyes, Hexanchidae) no oceano Atlântico sudoeste - Martín Cuevas, Juan; Gómez, Sebastián; Palacio, Cecilia; L. García, Mirta (Arquivos de Ciências do Mar, 2023)
A new record of Hexanchus griseus is reported for the coast of Argentina in Patagonia (45° 36´32.73´´S - 67° 16´ 33.68 W) at a depth of 19 m and with water temperature at 15.4°C. The specimen was a female captured, tagged and released inside a Marine Protected Area by local recreational fishermen as part of a national citizen science project. The specimen was a juvenile of 284.1 cm total length and it also constitutes the first tagged individual in the Southwest Atlantic Ocean for this species. Keywords: Hexanchus griseus, sixgill shark, Argentina, recreational fishery, citizen science, tagging, juvenile.